The ratio of the civil and civil-procedural legal relations in the science of civil procedural law - Didenkо, L. V.; Andreichenko, S. S.; Chebotareva, G. V.; Denysova, A. V. (Lviv-Toruń : Liha-Pres, 2019)
The article deals with the analysis of the relationship between civil and civil procedure. The categories of civil and civil procedural law, civil and civil procedural norms are compared, as well as the concepts of civil and civil procedural relations are established. The connection between civil and civil proceedings has been established. The author examines the features that are sectoral criteria for the relationship between civil and civil proceedings. The author has established the ratio of civil and civil legal relations according to certain criteria. They should be divided into general and special ones. The author emphasizes that by examining the relationship between civil and civil proceedings, we have come to the conclusion that both types of legal relationships are very close and closely interacting, although they are characterized by a number of significant differences.
Didenko L. V. The ratio of the civil and civil-procedural legal relations in the science of civil procedural law. New tasks and directions for the development of juridical science in XXI century : collective monograph / S. S. Andreichenko, G. V. Chebotareva, A. V. Denysova, L. V. Didenko, etc. Lviv-Toruń : Liha-Pres, 2019. - P. 49-65.
Keywords: relationship between civil law and civil procedural law; criteria for the ratio of civil law and civil procedural relations